Cardiovascular effects of GR117289, a novel angiotensin AT1 receptor antagonist. - Hilditch, A. (1994)
1. The effect of GR117289, an angiotensin AT1 receptor antagonist, on diastolic blood pressure (DBP) was determined in angiotensin-dependent and angiotensin-independent models of hypertension in rats. In addition, the antagonist profile of GR117289 at angiotensin AT1 receptors was determined in conscious renal hypertensive rats and conscious normotensive rats, dogs and marmosets. 2. Intra-arterial and oral administration of GR117289 (0.3-3 mg kg-1, i.a.; 1-10 mg kg-1, p.o.) to 6-day left renal artery ligated hypertensive (RALH) rats (DBP > 140 mmHg) produced significant, dose-related reductions in DBP with little apparent effect on heart rate (< 15%). The antihypertensive effect of GR117289 developed progressively over several hours and with some doses persisted for 24-48 h after administration. 3. Administration of GR117289 (1 mg kg-1, i.a.) on 5 consecutive days to RALH rats reduced DBP on each day. The antihypertensive effect of GR117289 was not cumulative as DBP had almost returned to base-line values, 24 h after administration of each dose. 4. A dose of GR117289 (3 mg kg-1, i.a.), which produced a substantial reduction in DBP (about 70 mmHg) in RALH rats, was administered to rats in which blood pressure was elevated either by unilateral renal artery clipping, sustained infusion of angiotensin II (AII), DOCA-salt administration or genetic inbreeding. GR117289 reduced DBP in rats in which the renin-angiotensin system was activated by renal artery clipping or AII infusion but had little effect in normotensive rats, DOCA-salt rats and SHR.(ABSTRACT TRUNCATED AT 250 WORDS)